Оптимизация периодичности ремонтов оборудования энергообъектов с учетом фактора старения - Ефимов, Александр Вячеславович; Потанина, Татьяна Владимировна (НТУ "ХПИ", 2014)
В исследовании представлен метод принятия решений о выборе стратегии технического обслуживания и ремонта оборудования энергоблоков электростанций. Описаны общие процедуры оценки и управления техногенным риском, включающие декомпозицию сложной технической системы, ранжирование оборудования по уровню риско-значимости (оценка риска, оценка последствий отказов), выводы о безопасности системы, методы управления риском. Рассмотрена математическая модель оптимизации продолжительности межремонтных периодов с учетом риска и фактора старения оборудования. Классификация состояния оборудования, включая «промежуточные», осуществлена с помощью модели Kijima и Sumita.

This investigation presents the method of decision making on the selection of the strategy of technical maintenance and repair of the equipment of the power units of power stations. A scheme for the assessment of artificial risk and risk control has been described. This scheme includes the decomposition of a complicated technical system, ranging the equipment in terms of riskimportance (risk estimation, assessment of failure after-effects), conclusions made on the safety of elements and system on the whole, and the methods of the risk control, in particular operative control, diagnostic tests, technical maintenance, and repair jobs. This paper describes the mathematical model used for the optimization of the duration of the periods between the repairs taking into consideration the equipment aging factor. The optimization of restoration jobs allows us to obtain such a result at lower losses. A criterion has been selected to establish the range of repair jobs, in particular the level of artificial risk, which is lower than the adopted admissible level. The costs required for the realization of the considered strategy of technical maintenance should be assessed including the operating costs and the costs related to the situation of adverse outcome, which is measured by the critical consequences of the failures of equipment required for the power station operation. A criterion of the decision making is to reduce to a minimum equipment failure costs taking into consideration the expenses and the possibility of the occurrence of failure scenario. The classification of equipment states, including the "intermediate" ones was performed using Kijima and Sumita models.
Optimization of the periodicity of the equipment repair for power facilities taking into consideration the aging factor
Keywords: эксплуатация; межремонтный период; восстановление; риск; power equipment; operation; repair period; restoration; risk; aging